Phenotypic Interindividual Differences in the Dynamic Structure of Sleep in Healthy Young Adults - Kishi A; Van Dongen HPA (Nature and Science of Sleep, 2023)
Akifumi Kishi,1– 3 Hans PA Van Dongen4,5 1Graduate School of Education, The University of Tokyo, Tokyo, Japan; 2Graduate School of Medicine, The University of Tokyo, Tokyo, Japan; 3Japan Science and Technology Agency, PRESTO, Saitama, Japan; 4Sleep and Performance Research Center, Washington State University, Spokane, WA, USA; 5Department of Translational Medicine and Physiology, Washington State University, Spokane, WA, USACorrespondence: Akifumi Kishi, Graduate School of Medicine, The University of Tokyo, 7-3-1 Hongo, Bunkyo-ku, Tokyo, 113-0033, Japan, Tel +81-3-5841-3415, Fax +81-3-5841-3418, Email kishi@p.u-tokyo.ac.jpIntroduction: Evaluating the dynamic structure of sleep may yield new insights into the mechanisms underlying human sleep physiology.Methods: We analyzed data from a 12-day, 11-night, strictly controlled laboratory study with an adaptation night, 3 iterations of a baseline night followed by a recovery night after 36 h of total sleep deprivation, and a final recovery night. All sleep opportunities were 12 h in duration (22:00– 10:00) and recorded with polysomnography (PSG). The PSG records were scored for the sleep stages: rapid eye movement (REM) sleep; non-REM (NREM) stage 1 sleep (S1), stage 2 sleep (S2), and slow wave sleep (SWS); and wake (W). Phenotypic interindividual differences were assessed using indices of dynamic sleep structure – specifically sleep stage transitions and sleep cycle characteristics – and intraclass correlation coefficients across nights.Results: NREM/REM sleep cycles and sleep stage transitions exhibited substantial and stable interindividual differences that were robust across baseline and recovery nights, suggesting that mechanisms underlying the dynamic structure of sleep are phenotypic. In addition, the dynamics of sleep stage transitions were found to be associated with sleep cycle characteristics, with a significant relationship between the length of sleep cycles and the degree to which S2-to-W/S1 and S2-to-SWS transitions were in equilibrium.Discussion: Our findings are consistent with a model for the underlying mechanisms that involves three subsystems – characterized by S2-to-W/S1, S2-to-SWS, and S2-to-REM transitions – with S2 playing a hub-like role. Furthermore, the balance between the two subsystems within NREM sleep (S2-to-W/S1 and S2-to-SWS) may serve as a basis for the dynamic regulation of sleep structure and may represent a novel target for interventions aiming to improve sleep.Keywords: polysomnography, sleep stage transitions, NREM/REM sleep cycles, ultradian rhythm, sleep phenotype